Dynamic duos: learning to care as a pair in the biparental prairie vole (Microtus ochrogaster) - Hinton, Taylor D.; Waugh, Rebecca E.; Sederberg, Per B.; Connelly, Jessica J.; Perkeybile, Allison M. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionA growing body of evidence shows that paternal care has long-lasting impacts on the social behavior of offspring, both in humans and other mammalian biparental species. However, fatherhood has historically been understudied and the dynamics of parental care adjustments based on their partner’s behavior remain unclear. This study investigates how individuals adjust parenting behavior based on their experience as part of a parenting dyad in the biparental prairie vole (Microtus ochrogaster).MethodsWe investigated how prairie voles learn to be parents by observing how their parental care effort changes over two consecutive litters. The first litter represents a naive context while the second litter represents an experienced context.ResultsOn average, dyads provided 9% more care in the naive context than in the experienced context. Experienced mothers, as a group, tended to reduce care significantly, while experienced fathers did not. By comparing the correlation between mother and father care in the naive versus experienced contexts, we found that parental care became more negatively correlated following experience. Finally, we investigated whether the difference in the amount of care provided by each parent in the dyad in the naive context drives the observed changes in experienced parental behavior, and found that these differences significantly predict the likelihood of reducing or increasing parental care effort in the experienced context for both the male and female partner.ConclusionOur results indicate that individual care behavior is adjusted based on the parenting effort of the dyadic partner. When only group-wise analyses are conducted, it appears that only mothers reduce care based on experience. However, through a dyadic-based analysis, we find that a larger difference in care between the two parents in the naive context corresponds to greater shifts in care by both parents in the experienced context. In sum, two patterns emerge in experienced parents that appear to improve parental care efficiency: (1) parents take on a more compensatory pattern of caregiving over time and (2) are able to adapt to initial differences in care such that investments in care become more balanced between mothers and fathers over time.